EGOLOGY AND ITS DECONSTRACTION. - Rechych, L. L. (Hileya: Scientific Bulletin / Gileya, 2019)
Subjective idealism is in crisis today, but few know how this crisis began. This paper propose to cast an eye back to such proponents of subjectivism as Rene Descartes and Edmund Husserl to trace their main arguments and most profound vulnerabilities. To demonstrate their weaknesses, this paper looks to the most up–to–date critical strategies represented by Jean–Luc Marion and Alfred Schütz. This will help uncover that the most dangerous threat for subjective idealism is not neurosciences but the concept of intersubjectivity.